Exploring the Structures and Functions of Macromolecular SLX4-Nuclease Complexes in Genome Stability - Payliss, Brandon J.; Patel, Ayushi; Sheppard, Anneka C.; Wyatt, Haley D. M. (Frontiers in Genetics, 2021)
All organisms depend on the ability of cells to accurately duplicate and segregate DNA into progeny. However, DNA is frequently damaged by factors in the environment and from within cells. One of the most dangerous lesions is a DNA double-strand break. Unrepaired breaks are a major driving force for genome instability. Cells contain sophisticated DNA repair networks to counteract the harmful effects of genotoxic agents, thus safeguarding genome integrity. Homologous recombination is a high-fidelity, template-dependent DNA repair pathway essential for the accurate repair of DNA nicks, gaps and double-strand breaks. Accurate homologous recombination depends on the ability of cells to remove branched DNA structures that form during repair, which is achieved through the opposing actions of helicases and structure-selective endonucleases. This review focuses on a structure-selective endonuclease called SLX1-SLX4 and the macromolecular endonuclease complexes that assemble on the SLX4 scaffold. First, we discuss recent developments that illuminate the structure and biochemical properties of this somewhat atypical structure-selective endonuclease. We then summarize the multifaceted roles that are fulfilled by human SLX1-SLX4 and its associated endonucleases in homologous recombination and genome stability. Finally, we discuss recent work on SLX4-binding proteins that may represent integral components of these macromolecular nuclease complexes, emphasizing the structure and function of a protein called SLX4IP.